Some Simplification of Complete System of Transformations for Proper Edge Colourings of Bipartite Graphs - Mirumyan, Alisa K. (Mathematical Problems of Computer Science, 2024)
In the investigation of a set of combinatorial objects, an important problem is to find a complete system of transformations. In this article a set of (k+1)-colourings of an arbitrary bipartite graph are considered. It is prooved that 2-transformation is a complete system of transformations for this type of set.